Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)
Location, Aim Long Island, 55 km north of New Guinea, erupted explosively in the seventeenth century and has been recolonized by animals and plants. Effectively in 1968, an island, Motmot, emerged from Long's 13 km‐diameter fresh‐water caldera lake, about 4 km from the nearest shore. A nested pair of colonization sequences is thus available for study. Long Island has been recolonized by birds, and Motmot has been colonized, presumably from the surrounding ring of Long Island. In order to monitor further colonization of Long Island following bird surveys in 1933 and 1972, and to survey the birds of Motmot, Motmot and the western parts of Long were visited for 15 days in 1999. Results In the last 66 years one species probably has become extinct; in the past 27 years three species have colonized and three, present in 1972, were not recorded in 1999. We assess the present number of nonmigrant land bird species as fifty. On Motmot, we recorded eight species, three breeding, and found two more only as prey remains (three raptor species were seen on the island). Main conclusions Long Island's avifauna still has youthful features. Species with good colonizing ability predominate, and there are no island‐endemic subspecies. There is a persistently high proportion of supertramps; none of the ten supertramps has been replaced by later‐colonizing ‘high‐S' species. A quasi‐equilibrium of about fifty species, fourteen fewer than the predicted equilibrium number for the island, has persisted for at least seven decades and may be seen as that appropriate to the present prolonged stage of Long's floral and vegetational development. Compared with the younger avifauna of Krakatau, Long's avifauna has a higher proportion of nectarivores, predators of large invertebrates and small vertebrates, and ground‐foraging insectivore‐herbivores, and a lower proportion of the insectivore‐frugivore guild. Motmot's small avifauna consists predominantly of species obtaining subsistence from outside the island.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. III. Colonization by birds - Clinton Schipper; Mike Shanahan; Simon Cook; Ian W. B. Thornton (Journal of Biogeography, 2001)